DEFINITION AS A GENRE IN THREE LEGAL SYSTEMS: A COMPARATIVE ANALYSIS - Vecchiato, Virginia (Comparative Legilinguistics, 2020)
This paper aims at comparing the definition of ‘trademark’ in three different legal systems – EU law, international law and US common law – in order to identify the discoursal, generic and textual characteristics of definition as a genre. The selected corpus of analysis is made up of three definitions from EU Regulation 2017/1001, WTO Agreement on Trade-Related aspects of Intellectual Property Rights (TRIPS) and US Lanham Act (sec.45) and of several US cases from 1926 to 2019. The theoretical framework within which the analysis is carried out is the seminal work on definition as carried out by Richard Robinson (1954) and Harris and Hutton (2007). The approach is mainly linguistic, though a historical excursus on the concept of definition is provided as a necessary introductory premise. The findings support the theory that considers EU legal texts as a different genre (Robertson 2012) characterised by a hybrid style (Robertson 2010) further emphasised in the definitional sections here analysed where EU term formation and definition result text-driven (Šarčević 2016). EU legal texts in their English version originate from the dynamic combination of two aspects: one connected to EU legal English – which is not common law English – and one connected to matters of terminology, syntax and general structure which has a French origin.